1997
DOI: 10.1002/jlac.199719970739
|View full text |Cite
|
Sign up to set email alerts
|

Complexation Properties of Preorganized Receptor Molecules for Large, Neutral Guests

Abstract: Receptor molecules with a preorganized cavity were synthesized by combining two resorcin [4]arene and one calix[4]-arene building block. Based on predictions from a computational study which matches hosts and guests, several steroids, sugar derivatives, and alkaloids were selected for complexation studies. Experimentally the complexation of such guests by these receptor molecules was proven by 'H-NMR spectroscopy (association constants of 1.0-6.0 X 10' M-' in CDC1,). One of these receptors with four hydroxyl g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Both molecules, in particular the one which is not shown (molecule 2), exhibit severe disorder as a result of the flexible BnO and MOM residues. The torsion angle for rotation about the chirality axis, C(6)ÀC(1)ÀC(23)ÀC (24), in molecule 1 adopts a value of 878, whereas it is significantly narrowed to 658 in molecule 2, illustrating the well-known conformational flexibility of the 1,1'-binaphthalene moiety [60]. A satisfactory yield of ( S )-22 (up to 66%) was finally obtained by treatment of ( S )-21 with 5 equiv.…”
mentioning
confidence: 99%
“…Both molecules, in particular the one which is not shown (molecule 2), exhibit severe disorder as a result of the flexible BnO and MOM residues. The torsion angle for rotation about the chirality axis, C(6)ÀC(1)ÀC(23)ÀC (24), in molecule 1 adopts a value of 878, whereas it is significantly narrowed to 658 in molecule 2, illustrating the well-known conformational flexibility of the 1,1'-binaphthalene moiety [60]. A satisfactory yield of ( S )-22 (up to 66%) was finally obtained by treatment of ( S )-21 with 5 equiv.…”
mentioning
confidence: 99%
“…In the example 60 (Chart 30), four strong intramolecular hydrogen bonds between the linking acetamide and the oxygens of the acetal bridging were found to significantly rigidify the structure [112]. In the example 60 (Chart 30), four strong intramolecular hydrogen bonds between the linking acetamide and the oxygens of the acetal bridging were found to significantly rigidify the structure [112].…”
Section: Bi-cavitands and Clamshell Containersmentioning
confidence: 97%
“…Studies in many different solvents and solvent mixtures revealed that carcerand formation is templated by the solvent and no empty carcerands are formed [112,114]. Studies in many different solvents and solvent mixtures revealed that carcerand formation is templated by the solvent and no empty carcerands are formed [112,114].…”
Section: Carcerands and Hemicarcerandsmentioning
confidence: 99%
“…U-shaped receptor molecules 16 and 17, composed of either two calix [4]arenes and one resorcin [4]arene [43] or of one calix [4]arene and two resorcin [4]arenes [44] , have a cavity similar to that of holand 15, but are more flexible than holand 15. This allows them to accommodate the structural deformations probably necessary for complexation.…”
Section: Combinations Of Calix[4]arenes and Resorcin[4]arenesmentioning
confidence: 99%
“…The stereochemistry of these 1:2-calix-resorcin [4]arenes is perhaps influenced by intramolecular interactions leading exclusively to endo-endo isomers. Receptor molecule 17 (R ϭ ϪH) is selective for acylated five-membered sugars and quinine deriva-According to 1 H-NMR spectroscopy, these 1:2-calix-resorcin [4]arene receptor molecules selectively complex cer-tives [44] . From a dilution experiment a dimerization constant of K dimer of 11 tain corticosteroids, sugar derivatives, and alkaloids with association constants of (1.0Ϫ6.0) ϫ 10 2  Ϫ1 in CDCl 3 .…”
Section: Combinations Of Calix[4]arenes and Resorcin[4]arenesmentioning
confidence: 99%